Assimetria na transmissão de preços de cerveja - Andrade, Gustavo Lôpo (2017)
In several markets, cost hikes are passed through to consumers to a larger extent than cost reductions. This is a widely document phenomenon in the literature, yet under-explored in Brazil. Collusion is one of the theoretical explanations for that. This study examines pass-through asymmetry in the Brazilian beer market where in 2013 four major brewing companies held over 98% of the market. Our results indicate asymmetry insofar as cost hikes are passed through but cost reductions don’t seem to affect prices. Moreover, supermarkets pass-through cost hikes more strongly than bars and restaurants.